2003
DOI: 10.1038/nature01833
|View full text |Cite
|
Sign up to set email alerts
|

Climate change decreases aquatic ecosystem productivity of Lake Tanganyika, Africa

Abstract: Although the effects of climate warming on the chemical and physical properties of lakes have been documented, biotic and ecosystem-scale responses to climate change have been only estimated or predicted by manipulations and models. Here we present evidence that climate warming is diminishing productivity in Lake Tanganyika, East Africa. This lake has historically supported a highly productive pelagic fishery that currently provides 25-40% of the animal protein supply for the populations of the surrounding cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
471
2
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 634 publications
(488 citation statements)
references
References 20 publications
9
471
2
6
Order By: Relevance
“…4, and the amount of warming increases toward the surface, this recent increase in temperature below the depth of seasonal mixing can most probably be attributed to climate variability or change. Comparable climatic warming was observed in other African lakes (Halfman 1993;Hecky 1993;Plisnier 2000;O'Reilly et al 2003;Verburg et al 2003), as well as in other lakes around the world (e.g., Scheffer et al 2001).…”
Section: Discussionmentioning
confidence: 70%
“…4, and the amount of warming increases toward the surface, this recent increase in temperature below the depth of seasonal mixing can most probably be attributed to climate variability or change. Comparable climatic warming was observed in other African lakes (Halfman 1993;Hecky 1993;Plisnier 2000;O'Reilly et al 2003;Verburg et al 2003), as well as in other lakes around the world (e.g., Scheffer et al 2001).…”
Section: Discussionmentioning
confidence: 70%
“…This can be important when assessing the effects of environmental changes for conservation purposes or when planning changes in species management strategies. Climate change has recently been shown to lead to differences in different features of the variation in a lake environment (O'Reilly et al 2003). According to O'Reilly et al (2003), increasing water temperature and decreasing wind velocity at Lake Tanganyika has decreased seasonal mixing of the water column and consequently reduced primary production.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis conducted by Root et al (2003Root et al ( , 2005 has also revealed a discernible trend in the population of both animals and plants as a consequence of climate warming over the past century. O'Reilly et al (2003) provided further evidence that climate warming has the potential to modify aquatic biota and ecosystems through its influence on the stability of the water column and hence nutrient transport.…”
Section: Introductionmentioning
confidence: 99%